Pengaruh Kualitas Pelayanan, Kepuasan Pelanggan, Dan Citra Merek Terhadap Keputusan Menggunakan Transportasi Udara Lion Air Pada Bandar Udara Jalaluddin Gorontalo - Karundeng, Deby Rita; Suyanto, Mohamad Afan; Lamuda, Ilyas; Tolah, Trisnawaty Ismael (CV. ITTC INDONESIA, 2024)
This research aims to determine and analyze the influence of service quality, customer satisfaction, and brand image on the decision to use air transportation with Lion Air at Djalaluddin Gorontalo Airport. The sample consisted of 99 Lion Air air transportation users, all of whom were respondents using a multiple linear regression analysis model. Based on the analysis results, it is indicated that Service Quality has a positive and significant effect on the Decision to Use Lion Air Air Transportation, Customer Satisfaction has a positive and significant effect on the decision to use Lion Air air transportation, Brand Image has a positive and non-significant effect on the Decision to Use Lion Air Air Transportation, and Service Quality, Customer Satisfaction, and Brand Image have a positive and significant effect on the Decision to Use Air Transportation with Lion Air at Djalaluddin Gorontalo Airport.